FROM SHADOWS TO LIGHT: WOMEN AND THEIR CONTRIBUTION TO MATHEMATICS THROUGH TIME, FROM ANTIQUITY TO THE MOON - González, Nohelys Edith Díaz; Medina, Alcibíades; Galástica, Narciso (Seven Editora, 2025)
From the earliest civilizations to the present day, women have played a fundamental role in the development of mathematics. Despite the numerous barriers and discrimination, they have faced, their legacy has been silenced and relegated to the background for centuries due to gender bias and a lack of recognition of their contributions. Among them are the woman who used the identity of a man to gain admission to an analysis class, and the African- American mathematician who collaborated on the Apollo 11 mission; each of them interested in mathematics and supporting the world.DOI: https://doi.org/10.56238/sevened2025.021-085